Changes in Physcio-Chemical Properties of Soil in Yamuna Ravine due to Soil & Water Conservation Measures - Dhingra, R.K.; Bhushan, Ls.; Dhakre, J.S (Journal of Soil and Water Conservation, 2022)
Soil erosion is one of the factors causing degradation of land. Gullies represent the last stage of erosion and are most spectacular and damaging feature of the landscape. To rehabilitate gullies and ravines, presenting of grazing and other biotic interference is the first conservation meastar. It was observed that by prevention of biotic interference considerable impmventent in water characteristics and other soil properties took place in Minima ravine. Due to protection there was tremendous increase in organic 'natter content and water holding capacity of the soil. In other words, a rapid upgradation of these otherwise highly degraded land was set in as a result of removal of biotic interference front the sceneaey words: Gullies, ravine, water characteristic, conservation measures, biotic interference.)